Modelagem, simulação e otimização de um sistema de conversão de monóxido de carbono e produção de hidrogênio - Alcantara, Anelise Freire (2007)
This paper constitutes a study on the process of ammonia production, focused on the shift reactors, and an efficient mathematical model development and with viable computational implementation for these fixed bed reactors. The usage of model to analyse and optimize the shift process comprises a powerful and very relevant tool for the industrial sector. Currently, the shift reaction acquired magnitude further than the ammonia production; being used, for instance, to maximize the production of H2 for hydrotreatment, and CO2 for enhanced oil recovery (EOR). This development comprised the model adaptation and simulation in steady-state through adjustment of phenomenological model parameters from experimental data, in such a way one could predict the main variables which could help to follow the process. As a function of the operational complexity of an ammonia production unit, the high energy consumption, the integration of the different existing modules, and the influence of some particular process variables, an operational optmization study was proceeded from the use of the developed model. The shift system optimization consisted of analyzing the obtained energy gain through operational interventions in the shift reactors assuring viable maximum hydrogen production. The proposed model was well-fitted for a preliminary study of the system operational conditions, and it can be useful for an integrated simulation of the ammonia production unit, besides serving as aid for future on-line steady-state optimization work.